Thomas Garth, Rector of Charlton-on-Otmoor, 1615-1643: rake or reformer? - Jackson, C (Oxfordshire Architectural and Historical Society, 2008)
In November 1617 the churchwardens of Charlton-on-Otmoor presented a case at the archdeaconry court in Oxford against their new rector, Thomas Garth, for negligent ministry, scandalous behaviour, and sexual misconduct. The outcome of the case is not known, but Garth appears to have taken up residence and installed a wife and family in the parish, remaining as incumbent for a further twenty-five years. It was rare in the post-Reformation period for formal complaints to be made against clergymen, and the fact that the case was pursued so vigorously suggests that there were wider and more deep-seated tensions within the parish and the wider local community. His accidental involvement in a long-standing dispute concerning the lease of the rectory and glebe may have antagonized his parishioners, added to which it is possible that he was seen as an unpalatable force for godly reformation in a long-neglected and religiously conservative parish. This article examines the complaints voiced by Garth’s parishioners and locates them within the wider context of early modern parish life and the post-Reformation Church.